The median effective dose of esketamine with different doses of oliceridine during hysteroscopic surgery - Shi, Min; Wang, Tong; Wang, Weiwei; Wang, Jiafeng; Li, Lulu; Bo, Lulong; Wang, Xiaolin (Frontiers in Pharmacology, 2025)
PurposeThis study aimed to investigate the impact of different doses of oliceridine on the ED50 of esketamine during hysteroscopic surgery. The objective was to establish an optimal dosing regimen that facilitates the development of an effective and safe analgesic strategy for this procedure by leveraging the potential synergistic effects between the two drugs.MethodsThe trial was conducted involving 90 patients scheduled for elective hysteroscopy. Participants were allocated into three groups: control (0 mg oliceridine), group O1 (1 mg oliceridine), and group O2 (2 mg oliceridine). Anesthesia was induced with propofol, followed by a continuous infusion of propofol and a preset dose of esketamine. The primary outcome was the ED50 of esketamine, determined using Dixon’s up-and-down method. Secondary outcomes included recovery time, hemodynamic parameters, pain and sedation scores, and the incidence of adverse events.ResultsThe ED50 of esketamine was 0.76(0.66–0.86), 0.45(0.40–0.55), and 0.41 (0.31–0.59) mg/kg/h in the control, group O1 and O2, respectively. Compared with the control, group O1(P = 0.020) and O2(P = 0.001) showed significantly shorter recovery time. Hemodynamic stability was comparable across groups, though the effect on HR was observed: bradycardia incidence was higher in group O1 than in the Control (P = 0.021) but lower in group O2 than in O1(P = 0.004). Compared to the control, the O1 and O2 groups showed a significantly reduced incidence of both excessive oral secretion (3.7% in group O2 vs. 0.0% in group O1 vs. 32.0% in control, P = 0.000) and cough (4.3% in group O1 and 0.0% in group O2 vs. 28.0% in the control, P = 0.002). The combination therapy did not increase respiratory adverse reactions (P > 0.05), and the 2 mg of oliceridine appeared to provide optimal balance between efficacy and safety within the limits of this study.ConclusionFor hysteroscopic procedures, the co-administration of oliceridine was associated with a lower ED50 of esketamine. This regimen provided synergistic analgesia, reducing the ED50 of esketamine to lower deep sedation and accelerate recovery. Furthermore, it improved hemodynamic stability by lowering bradycardia incidence without augmenting respiratory adverse effects.Trial Registrationwww.chictr.org.cn, (ChiCTR2500101056); registration date: April 18, 2025.